2016
DOI: 10.3390/toxins8080234
|View full text |Cite
|
Sign up to set email alerts
|

Putative Nonribosomal Peptide Synthetase and Cytochrome P450 Genes Responsible for Tentoxin Biosynthesis in Alternaria alternata ZJ33

Abstract: Tentoxin, a cyclic tetrapeptide produced by several Alternaria species, inhibits the F1-ATPase activity of chloroplasts, resulting in chlorosis in sensitive plants. In this study, we report two clustered genes, encoding a putative non-ribosome peptide synthetase (NRPS) TES and a cytochrome P450 protein TES1, that are required for tentoxin biosynthesis in Alternaria alternata strain ZJ33, which was isolated from blighted leaves of Eupatorium adenophorum. Using a pair of primers designed according to the consens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
(43 reference statements)
0
10
1
Order By: Relevance
“…Cochliobolus miyabeanus was the first non-Alternaria species shown to produce tentoxin (de Bruyne et al, 2016). Tentoxin occurs in many Alternaria species and is known to induce chlorosis due to damage to the F 1 -ATPase of chloroplasts in sensitive plants (Li et al, 2016). Although the TES gene is present in the E. turcicum genome, read count values were low and do not indicate that tentoxin plays a role in pathogenicity of E. turcicum on maize.…”
Section: Discussionmentioning
confidence: 99%
“…Cochliobolus miyabeanus was the first non-Alternaria species shown to produce tentoxin (de Bruyne et al, 2016). Tentoxin occurs in many Alternaria species and is known to induce chlorosis due to damage to the F 1 -ATPase of chloroplasts in sensitive plants (Li et al, 2016). Although the TES gene is present in the E. turcicum genome, read count values were low and do not indicate that tentoxin plays a role in pathogenicity of E. turcicum on maize.…”
Section: Discussionmentioning
confidence: 99%
“…The tangerine pathotype of A. alternata produces host-selective ACT-toxin, the biosynthesis of which is essentially encoded by a polyketide synthase gene that is also required for pathogenicity of this fungus [34]. NRPS and cytochrome P450 protein TES1 are required for tentoxin biosynthesis in A. alternata strain ZJ33 [35], while the PKS gene ACRTS2 is responsible for host-selective ACR-Toxin biosynthesis in the rough lemon pathotype of A. alternata [36]. In the present study, DEGs corresponding to NRPS and PKS homologs were also identified, confirming the importance of this toxin synthesis during A. alternata invasion into chrysanthemum.…”
Section: Discussionmentioning
confidence: 99%
“…The tangerine pathotype of A. alternata produces host-selective ACT-toxin, the biosynthesis of which is essentially encoded by a polyketide synthase gene that is also required for pathogenicity of this fungus [33]. NRPS and cytochrome P450 protein TES1 are required for tentoxin (TEN) biosynthesis in A. alternata strain ZJ33 [34], while the PKS gene ACRTS2 is responsible for host-selective ACR-Toxin biosynthesis in the rough lemon pathotype of A. alternata [35]. In the present study, DEGs corresponding to NPRS and PKS homologs were also identi ed, con rming the importance of this toxin synthesis during A. alternata invasion into chrysanthemum.…”
Section: Discussionmentioning
confidence: 99%